(3GdebGeGJ GdLhRjI aj GdeYGfj GdhYXjI hTQM GdcdeGJ GddZhjIs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3MVQJ djdI eY QabI ef efJNH GdCUGOb, djS ajge GdqG efJNH UGOb s
(3BNQgG (B:s
(3hfMf fSCd hGgH Gdaghe, Cf jfaYfG HLejY GdYdhe, Efg hdj Pdc hGdbGOQ Ydjg HQMeJg s
(3fSNI QGHYIs
(3HgG fXGe GdJYbjHIs
(3jJab BNQgG eY BNQ GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs